Analisis Kinerja Keuangan dan Kontribusinya Bagi Kesejahteraan Masyarakat pada Pemerintah Kota Tangerang - Agustin, Stevani; Armeliza, Diah; Nasution, Hafifah (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This study aims to analyze financial performance measured using regional financial ratios and to analyze how financial performance contributes to community welfare. The Tangerang City Government serves as the research object. In the data collection process, this study employs secondary data, specifically the LKPD of the Tangerang City Government for the years 2018-2022, utilizing descriptive quantitative methods. The results of this study reveal that the financial performance of the Tangerang City Government is deemed satisfactory. These evidenced by a relatively high independence ratio attributed to the substantial realization of PAD, a strong decentralization ratio beacuse of consistent optimization of its regional potential, and an effectiveness ratio classified as highly effective due to consistently surpassing the predetermined revenue target/budget. However, the efficiency ratio of PAD is somewhat efficient, owing to the substantial costs incurred in collecting PAD and the fluctuating growth ratio due to the decline in 2020, caused by the impact of the COVID-19 pandemic. as to the contribution to community welfare, the Tangerang City Government allocates expenditures, particularly across four indicators/aspects (education, health, social, and labor) all of which display consistent growth, that allocation distributed in the programs and activities aimed at enhancing community welfare. A recommendation for future researchers is to consider employing primary data collection methods, such as direct interviews with community members or city government officials, to gain further insights into financial performance and its impact on community welfare.